Pengaruh Good Corporate Governance terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening - Virliandita, Berliana; Sulistyowati, Erna (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research objective to be achieved are to prove the effect of Good Corporate governance on firm value, prove the effect of Good Corporate governance on financial performance, prove the effect of financial performance on firm value, prove the effect of Good Corporate governance on corporate value through financial performance as an intervening variable in corporate bodies Sate Owned Enterprises listed on the Indonesia Stock Exchange in 2017-2021. The method used in this research is to use quantitative methods. Sampling of this study using purposive sampling obtained 13 sample. The analysis technique used in this research is path analysis using SPSS 25 software. Based on the research result, it can be seen that Good Corporate governance has no effect on company value, Good Corporate governance effects the financial performance, financial performance effects company value, Good Corporate governance influences company value through financial performance as an intervening variable in corporate bodies State Owned Enterprises listed on the Indonesia Stock Exchange in 2017-2021.